PENERAPAN PELAKSANAAN ANGGARAN PERCEPATAN PENDAFTARAN TANAH SISTEMATIS LENGKAP DI KABUPATEN TANGGAMUS - Herlina Ratna (KEADILAN PROGRESIF, 2019)
Systematic land registration according to Government Regulation Number 24 of 1997 isdefined as a series of activities carried out by the government in a sustainable, sustainableand orderly manner. The problem in this study is the implementation of a systematicsystematic land registration budget at the Land Office of Tanggamus Regency based onMinister of Agrarian Regulation and Spatial Planning No. 35 of 2016 concerning SystematicComplete Land Registration Acceleration. The method used by the normative juridicalapproach and analysis is carried out qualitatively. Budget implementation is based on theMinister of Agrarian Regulation and Spatial Planning No. 35 of 2016 concerning theAcceleration of Comprehensive Systematic Land Registration in Tanggamus Regency but notyet optimal, can be seen from the fact that there are still 10% of the budget that has not beenabsorbed from the budget available in the Budget Implementation List (DIPA) in 2019specifically for PTSL, matters this is because relatively little time periods are also limited tothe closing budget per year. The Government's suggestion in this case the TanggamusDistrict Land Office should further increase public awareness and education regarding theimplementation of the budget in the Systematic Complete Land Registration (PTSL), this isdone so that the public understands and understands the use of funds collected from thecommunity so as not to cause polemics in the future.